Methodological Tools for Risk Assessment in Industrial Enterprises - Ushvitskii, Lev I.; Kulagovskaya, Tat’yana A.; Ter-Grigor’yants, Anna A.; Solovyova, Irina V.; Mezentseva, Elena S. (International Journal of Economics and Financial Issues, 2015)
This article deals with methodological propositions for risk assessment in industrial enterprises on the basis of the theory of statistical modeling and planning from ultimate goals with account to optimal use of limited productive resources; instruments for grouping simple and complex risks according to their probability. Existing processes of economic instability stipulated some topical problems. Construction of the system of management of an economic entity that provides stable dynamics of its development depends on how we solve the problems. Problems of creating an effective system of economic-organizing measures to reduce negative impact of risk factors on their effectiveness are important for stable functioning of industrial enterprises. We can single out several causes of risk situations: impossibility to get exact knowledge about future, lack of information about the environment conditions, uncertainty of financial and economic activities, etc. Moreover industrial production has its specific features that require people making management decisions to do a thorough analysis of risks. These risks make an impact on functioning of economic agents to the utmost degree. It is important to be able to single out and systematize objective and subjective; external and internal; manageable and unmanageable; simple and complex risks and to provide objective and reliable appraisal of them in order. It should be done in order to reduce negative impact of uncertainty in market environment on conditions and results of implementation of economic processes. We should also remember that risks can cross each other, superimpose on one another or develop separately. Keywords: industry; risk; assessment; expert method; complex risks; simple risks; statistical modeling JEL Classifications: C13; D81; L51